Comparison of Al[18F]-NOTA-FAPI-04 PET/CT and [18F]-FDG PET/CT in a patient with lung cancer and pulmonary tuberculosis: a case report and literature review - Qin, Jingjie; Yu, Jinming; Wei, Yuchun (Frontiers in Oncology, 2025)
BackgroundThe coexistence of lung cancer and pulmonary tuberculosis (TB) makes differential diagnosis even more complicated. The purpose of the study is to explore superiority of [18F]-NOTA-FAPI-04 PET/CT in distinguishing TB from malignant lesions and accurately detecting inflammatory lymph nodes than [18F]-FDG PET/CT.Case summaryHerein, we described a case report of a patient with both lung cancer and tuberculosis underwent [18F]-FDG and Al[18F]-NOTA-FAPI-04 positron emission tomography/computed tomography (PET/CT) to determine staging. Additionally, a literature review was conducted to discuss the potential clinical applications of FAPI PET/CT. We reported a 70-year-old man with newly diagnosed lung squamous cell carcinoma underwent [18F]-FDG and Al[18F]-NOTA-FAPI-04 PET/CT to determine staging. The avid uptake of [18F]-FDG in old pulmonary TB and the right hilar inflammatory lymph nodes (<1 cm) were not found on Al [18F]-NOTA-FAPI-04 PET/CT. After 2 months of follow-up, the small lymph node was finally confirmed to be inflammatory.ConclusionAl[18F]-NOTA-FAPI-04 PET/CT may perform better in distinguishing TB from malignancy and may offer greater specificity than [18F]-FDG PET/CT for the diagnosis inflammatory lymph nodes.